1992
DOI: 10.3354/dao013203
|View full text |Cite
|
Sign up to set email alerts
|

Propentes of three iridovirus-like agents associated with systemic infections of fish

Abstract: Three iridovirus-like agents associated with systemic infections in fish were examined by electron microscopy, gel electrophoresis of virion polypeptides and serological cross reactions with hyperimmune rabbit sera. The virus associated with epizootic hematopoietic necrosis (EHN) of redfin perch Perca fluviatilis in Australia, the virus from sheatfish Siluris glanis in Germany and a recently isolated iridovirus-like agent from catfish Ictalurus melas in France shared similar virion morphology and size, number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 22 publications
2
65
0
1
Order By: Relevance
“…The application of serological tests is limited by the cross-reactivity of antibodies to all ranaviruses and the absence of a secondary test method to evaluate sensitivity and specifi city. Virus neutralization tests cannot be used because antibodies with neutralizing activity to EHNV were not evoked following immunization of rabbits (Hedrick et al 1992 ) or from mouse monoclonal antibodies (Monini and Ruggeri 2002 ). Current knowledge of the amphibian, reptile, and piscine immune systems indicates limitations to serological techniques that are imposed by a lack of affi nity maturation, poor immune memory, and temperature dependence of the response (McLoughlin and Graham 2007 ).…”
Section: Detecting Antibodies: Serologymentioning
confidence: 99%
See 1 more Smart Citation
“…The application of serological tests is limited by the cross-reactivity of antibodies to all ranaviruses and the absence of a secondary test method to evaluate sensitivity and specifi city. Virus neutralization tests cannot be used because antibodies with neutralizing activity to EHNV were not evoked following immunization of rabbits (Hedrick et al 1992 ) or from mouse monoclonal antibodies (Monini and Ruggeri 2002 ). Current knowledge of the amphibian, reptile, and piscine immune systems indicates limitations to serological techniques that are imposed by a lack of affi nity maturation, poor immune memory, and temperature dependence of the response (McLoughlin and Graham 2007 ).…”
Section: Detecting Antibodies: Serologymentioning
confidence: 99%
“…Secondary antibodies suitable for immunofl uorescence or enzymatic detection enable the detection of ranavirus antigens in tissue sections and cell cultures (Reddacliff and Whittington 1996 ). Some antisera are directed against the MCP and are cross-reactive; thus, all ranaviruses can be detected, but it is not possible to distinguish between ranaviruses (Hedrick et al 1992 ;Ahne et al 1998 ). Other antisera have been developed against purifi ed virions (Balseiro et al 2009 ), but again, it might not be possible to distinguish between ranaviruses.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Four genera are currently recognized: two genera, Iridovirus and Chloriridovirus, infect only invertebrates whereas members of a third genus, Lymphocystivirus, infects a variety of freshwater and marine fish causing self-limiting tumor-like masses in the skin (Williams, 1996). Viruses belonging to the fourth genus, Ranavirus, were originally thought to infect only amphibians (Granoff et al, 1965;Wolf et al, 1968) but recently iridovirus isolates from fish and reptiles have been shown to be more closely related to frog virus 3 (FV3), the type species of the genus Ranavirus, than to Lymphocystivirus (Hedrick et al, 1992a;Mao et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Fish iridoviruses of the estab lished genera Lymphocystivirus and "Goldfish virus 1 -like viruses" of the family Iridoviridae do not cause systemic infection in fish. In addition, EHNV and SFIV were shown to have strong affinities to members of the genus Ranavirus in the family Iridoviridae (Hedrick et al, 1992). Therefore, there is a possibility that RSIV belongs to the group that is separated from previously reported genera such as Ranavirus, Lymphocystivirus and "Goldfish virus 1-like viruses".…”
Section: Discussionmentioning
confidence: 91%